The Loss of Spain: A Symptom in Poema de Fernán González and Estoria de Espanna. - Iglesias-Crespo, Carlos (Hispanic Research Journal, 2022)
This article offers a comparative study of the emplotment of the Loss of Spain in the Poema de Fernán González and in Alfonso X’s Estoria de Espanna. A study on their sources and genres is followed by an examination of their ideological premises in order to foreground the reasons behind their manifest divergences in the treatment of the Loss, focused on the conceptualization of treason and the role of Count Don Julián. The results provide fresh insight into how these works negotiate their anxieties over power, legality, legitimacy, and religion in the age of the Learned King.